Clinical Research Using Salviae Miltiorrhizae Radix-Pharmacopuncture for Lumbar Herniated Intervertebral Disc: Analysis of Trends - Seon Woo Kim; Cheol Woo Park; Myeong Jae Jo; Min Wook Kim; Jae Hee Yu; Jeon Seok Hee; Seung Won Jang; Do Young Kang; Hyun Jin Jeong (MEDrang Inc., 2021)
This review of national and international randomized controlled trials of Salviae miltiorrhizae radix pharmacopuncture for lumbar herniated intervertebral discs was performed to assess its clinical efficacy. There were 5 online databases (PubMed, EMBASE, CNKI, NDSL, OASIS, and RISS) searched on June 1st, 2020. Studies were selected according to the inclusion and exclusion criteria and were reviewed by risk of bias assessment. This review included 14 Chinese studies. The sample sizes ranged from 50 to 100. The numbers of treatments ranged from 20 to 30, with most patients receiving 20 treatments. The longest treatment periods were 10-15 and 15-20 days, of which each accounted for 29% of the studies. The most frequently used evaluation indices were the Japanese Orthopedic Association and the Visual Analog Scale scoring method. The most frequently used acupoints were EX18 and BL25, which accounted for 31% of the total number of acupoints. In 50% of the studies, the pharmacopuncture injection volume was 2 mL. Acupuncture treatment was the most common control group. Eleven studies reported that the intervention group had significantly improved symptoms. However, most of the included studies were of low quality.